Efficacy and Safety of Enteral Human Recombinant Insulin to Reduce the Time to Full Enteral Feeding in Preterm Infants: A Meta-Analytical Study - Faiza Qudsia; Muhammad Adil; Maha Kamran; Muhammad Azam; Huzaifa Ahmad Cheema; Abia Shahid; Ivan Cherrez-Ojeda (MDPI AG, 2023)
Recombinant human insulin plays an important role in the gut maturation of preterm infants. This meta-analysis was carried out to assess the efficacy and safety of enteral recombinant human insulin in decreasing the time to full enteral feeding in preterm infants. The pooling of data from four clinical trials yielded a significant decrease in the time to full enteral feeding in preterm infants under both low (Mean difference [MD] −3.43 days; 95% CI: −6.18 to −0.69 days; I2 = 48%) and high doses of insulin (MD −7.10 days; 95% CI: −10.02 to −4.18 days; I2 = 0%). These findings require confirmation by further large trials that evaluate the efficacy and safety of enteral insulin, especially at supraphysiological doses.